Development of Floating Solar Panel Efficiency and Their Maintenance - SAZALI, NURFARHANNAH; Lam Hong Yin; Sumaiya Mashori (Progress in Engineering Application and Technology, 2025)
Floating photovoltaic (FPV) systems offer a promising alternative to traditional ground-mounted solar panels by leveraging water surfaces to improve efficiency, conserve land, and reduce water evaporation. Despite their advantages, FPV systems face challenges such as overheating, dirt accumulation, and increased maintenance needs, which hinder their widespread adoption. This study addresses these limitations through the development of an innovative FPV system equipped with a 12V water pump for automated cooling and cleaning, monitored via an Internet of Things (IoT) platform. The methodology involves integrating the cooling and cleaning mechanisms into the FPV system, utilising IoT for real-time monitoring and control. Experiments were conducted to evaluate the system’s performance under varying environmental conditions. Key performance metrics, such as temperature regulation, energy output, and cleaning efficiency, were compared to those of ground-mounted PV systems. Results demonstrate that the FPV system, with automated cooling and cleaning, consistently outperforms traditional systems. Cooling mechanisms reduced panel temperatures by up to 5°C, leading to a 10–15% increase in energy output. The cleaning system effectively removed up to 90% of dust, restoring panel efficiency within seconds. This research highlights the potential of FPV systems in advancing renewable energy technologies by improving efficiency, reducing maintenance, and promoting sustainability. Future work will focus on optimising materials for harsh environments, scaling the system for diverse aquatic settings, and evaluating its environmental impact. The findings underline the importance of supportive policies to drive the adoption of FPV systems as a viable solution for global energy demands.